Soybean Oil-Quality Variants Identified by Large-Scale Mutagenesis - Karen Hudson (International Journal of Agronomy)
To identify genetic variation for fatty acid composition in mature soybean seeds, 4566 M3 generation seed samples from a chemically mutagenized population were subjected to fatty acid profiling by gas chromatography. In the population, a wide range of variation in the content for each of the five major fatty acids was observed. Seventy-nine lines were identified which contained significantly high or low levels of one of the five major soybean fatty acids. These lines were advanced to the subsequent generation. Of the 79 lines showing a variant fatty acid profile in the M3, 52 showed clear heritability for the oil composition in the seeds of the subsequent generation. These lines are likely to represent 52 distinct genetic mutations. These mutants may represent new loci involved in the determination of soybean seed oil content or could be new isolates or alleles of previously identified genetic variants for soybean oil composition.